Tunas Depati Amir Athletes Concentration Levels During Training - M Rangga Ade Kurnia; Dzihan Khilmi Ayu Firdausi; Agung Prayoga Budiargo; Febry Framuliya; Irhas Mahmudi; Eza Junianda Pratama (Jurnal Pendidikan Jasmani (JPJ), 2023)
The problem in this research is the level of concentration of football athletes during practice. The purpose of this study was to find out the level of concentration of soccer athletes while doing exercises where the research data is based on the opinions of the athletes themselves. The subjects in this study were 37 children of SSB Tunas Depati Amir Pangkal Pinang, Bangka Belitung. The description in this study is intended to describe the results of data collection, namely about the respondents' answers to measure the level of concentration of football athletes in training. The data to identify the level of concentration of the athlete of Sepak Tunas Depati Amir is expressed in 23 questions about the level of concentration divided into 3 aspects, namely recognizing the level of concentration in oneself, internal concentration, and external concentration. Based on the table above, it shows that the percentage level of concentration of football athletes is based on factors; recognize the level of concentration on oneself, internal concentration, external concentration, namely from the factor of recognizing the level of concentration on oneself with a percentage of 81.75% and included in the "very good" category, the internal concentration factor with a percentage of 69.74% and included in the "good" category ”, then the external concentration factor with a percentage of 72.69% and is included in the “good” category. Based on data analysis, description, testing of study findings, and debates, the following conclusions can be drawn the concentration level of Tunas Depati Amir soccer athletes is in the good category.